Dioxin/furan level in the Malaysian oil palm environment - Tuan Fauzan Tuan Omar,; Ainie Kuntom,; Aishah A. Latiff, (Universiti Kebangsaan Malaysia, 2013)
Environmental samples collected from oil palm premises were evaluated for dioxins/furans contamination. The samplings were carried out at oil palm premises located in Banting (Premise A) and in Teluk Intan (Premise B), involving two environmental matrices namely ambient air and soil. The soil samples were collected in the plantations while ambient air samples were collected in the vicinity of the mills and refineries. The results of the analyses showed that the level of dioxins/furans in ambient air were generally higher in oil palm premise located adjacent to industrial establishments. The concentration levels at premise A mill and refinery located adjacent to industrial establishments, ranged from 64.14 WHO–TEQ fg m-3 to 131.87 WHO–TEQ fg m-3, while for premise B mill and refinery located in the rural area, ranged from 9.93 WHO–TEQ fg m-3 to 16.66 WHO–TEQ fg m-3. Meanwhile for soil samples, the highest concentrations were recorded in soil collected near roads used heavily by vehicles. The concentration levels of soil samples collected at premise A and premise B plantations ranged from 1.910 WHO-TEQ pg g-1 dry weight to 3.305 WHO-TEQ pg g-1 dry weight.